KAPABILITAS INSTITUSI MILITER DALAM MENGATASI PELANGGARAN UDARA: STUDI PADA LANUD ROESMIN NURJADIN DALAM PENGGUNAAN AIR COMBAT MANEUVERING INSTRUMENTATION (ACMI) WING 6 - Idris, Idpianto; Sudirman, Arfin; Sulaeman, Dina Y (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The capability of Roesmin Nurjadin Air Force Base in utilizing Air Combat Maneuvering Instrumentation (ACMI) Wing 6 plays a crucial role in addressing violations of national airspace. This research aims to explore the capabilities of Lanud Roesmin Nurjadin in utilizing ACMI Wing 6 and to identify efforts that can be made to enhance them. The research problem includes the operational capabilities of ACMI Wing 6 and the challenges in addressing violations of national airspace. Factors such as technical limitations, personnel training, and supporting infrastructure are the main focus of the analysis. The research method used is qualitative, characterized by descriptive analysis. This research obtained data through interviews with several relevant informants, documentation studies, internet-based studies, and archival studies aimed at collecting data related to the capabilities of Lanud Roesmin Nurjadin in utilizing ACMI Wing 6. The research results indicate that Roesmin Nurjadin Air Base has sufficient operational capability in using ACMI Wing 6. However, there are still several technical challenges, personnel training issues, and supporting infrastructure that need to be addressed. This study finds that Roesmin Nurjadin Air Base has the potential to enhance its capabilities in using ACMI Wing 6 by improving supporting infrastructure, increasing personnel training, and overcoming technical obstacles. Although the ACMI operator personnel have good technical skills, there is a need to enhance conceptual analysis abilities, especially regarding responses to violations of national airspace. The teamwork among ACMI personnel is very good, demonstrating readiness to face emergency situations and complex airspace violations